2015
DOI: 10.1007/s00405-015-3742-2
|View full text |Cite
|
Sign up to set email alerts
|

FNAC and frozen section correlations with definitive histology in thyroid diseases

Abstract: The ability to diagnose thyroid cancers pre-op or intra-operatively by fine needle aspiration cytology (FNAC) or frozen section (FS) leads to the delivery of appropriate one-stage surgical management. We aim to study the concordance and discordance of FNAC and FS with final histology in thyroid pathologies. All thyroid procedures from 2007 to 2011(n = 423), involving FNAC and or frozen section in their management pathway were included. FNAC (n = 159) were classified in a five-tier system (Nondiagnostic, Benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…[28][29][30] However, several recent series report very low sensitivities, ranging from 22% to 51%. 31,32 In a recent review, Najah and Tresallet 33 concluded that FSs contributed little to the diagnosis of undetermined thyroid nodules due to their low sensitivity and high false negative rates. They suggested that tumor capsular invasion, which is the hallmark to diagnose malignancy, could not be evaluated on FSs, and was only possible on permanent sections.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] However, several recent series report very low sensitivities, ranging from 22% to 51%. 31,32 In a recent review, Najah and Tresallet 33 concluded that FSs contributed little to the diagnosis of undetermined thyroid nodules due to their low sensitivity and high false negative rates. They suggested that tumor capsular invasion, which is the hallmark to diagnose malignancy, could not be evaluated on FSs, and was only possible on permanent sections.…”
Section: Discussionmentioning
confidence: 99%
“…FS only altered the initial surgical plan in 7.5% cases. This compares with a rate of 0‐62% in the literature, 9‐20 with studies significantly affected by patient factors, surgeon preference and selection bias. The only preoperative measure that significantly correlated with a “positive” FS in our cohort was an USGFNA result of “suspicious for malignancy” (Thy 4/Bethesda V).…”
Section: Discussionmentioning
confidence: 70%
“…An extensive amount of literature has been published on the utility of intraoperative FS and its correlation to preoperative USGFNA results. The results and conclusions of these papers are largely influenced by their cohort characteristics and pathology 9‐20 . Our institution represents a high‐volume tertiary care centre with dedicated endocrine pathologists.…”
Section: Introductionmentioning
confidence: 99%
“…Mayooran et al showed a clear correlation between FNB and frozen section with the definitive histology of thyroid cancer and concluded that “FNAC [abbreviation of: fine-needle aspiration cytology] is considered as the best modality to triage the thyroid nodule preoperatively,” and that “the intraoperative frozen sections are helpful to perform a one-stage operation for suspicious thyroid lesions” [ 13 ]. It is therefore unfortunate to notice that the present investigation of clinical practice in perioperative diagnostics in thyroid cancer patients reveals quite similar numbers as in the aforementioned previous studies [ 2 ].…”
Section: Discussionmentioning
confidence: 99%